Review the implementation waste management practices in construction work around Taman Indera Sempurna, Pekan-Kuantan, Pahang Darul Makmur - Mohd Nurarif, Zulhemay (2012)
The construction waste has been identified as one of the major contributors to the solid waste and hence contributed to the environmental impacts in both developed and developing countries. As a result, the waste management becomes the important function of construction project management in order to reduce the volume of waste on site. Waste management has been grouped under three main group’s namely waste classification, waste management approaches and waste disposal technologies. Nevertheless, these approaches give less intention in the waste management on construction site. The study was carried out to analyze the waste handling processes in three selected construction site around Taman Indera Sempuma, Pekan-Kuantan, Pahang Darul Makmur by using the free flow mapping methods. The analysis leads to develop a waste management mapping model (WMMM), which incorporates the good practices embodied in the existing practices. The WMMM provides an alternative tool assisting in waste handling processes on construction sites. It can be a medium for comparing the waste management practices between construction sites, thus both good practices and weaknesses can be identified. Besides, it provided a level of indication about the current practice of waste management on construction sites.